Intervention to reduce unnecessary urinary catheter use in a large academic health science centre: A one‐group, pretest, posttest study with a theory‐based process evaluation. Issue 2 (14th May 2021) - Backman, Chantal; Wooller, Krista R.; Hasimja‐Saraqini, Delvina; Demery Varin, Melissa; Crick, Michelle; Cho‐Young, Danielle; Freeman, Lisa; Delaney, Lori; Squires, Janet E.
Abstract: Aim: To evaluate an intervention to reduce unnecessary urinary catheter use and prevent catheter‐associated urinary‐tract infections (CAUTI) in hospitalized patients across an academic health science centre. Methods: We conducted a one‐group, pretest, posttest study with a theory‐based process evaluation. Phase 1 consisted of a pre/postintervention to test the impact of a CAUTI protocol. Audits on four units were conducted, and data were analysed descriptively. Phase 2 consisted of a theory‐based process evaluation to understand the barriers/enablers to the implementation. Semistructured interviews were conducted and then analysed using a systematic approach. Results: In Phase 1, all inpatients with urinary catheters admitted to the units ( N  = 4) during the study period ( N  = 99, pre) and ( N  = 99, post) were included. CAUTI prevalence rate was 18.2% pre versus 14.1% post ( p  = .563). In Phase 2, participants ( N  = 18) who worked on the units were interviewed, and a total of 13 barriers and 19 enablers were found.